The effect of an experimental decrease in salinity on the viability of the subarctic planktonic foraminifera Neogloboquadrina incompta - Greco, Mattia; Meilland, Julie; Zamelczyk, Kasia; Rasmussen, Tine Lander; Kucera, Michal (Polar Research, 2020)
Chemical signatures in the calcite of shells of polar and subpolar planktonic foraminifera have been frequently used to trace and quantify past meltwater discharge events. This approach assumes that the foraminifera can tolerate low salinity under extended periods. To obtain a first experimental constraint on salinity tolerance of Subarctic foraminifera, we carried out a culturing experiment with specimens of the subpolar species Neogloboquadrina incompta collected in the northern Norwegian Sea off Tromsø in October 2018. The foraminifera were exposed to a gradient of salinities between 35 and 25 PSU. Survival was monitored over 26 days by measuring the extent of the rhizopodial network. Although chamber growth only occurred in one of the observed specimens, likely due to the largely unknown dietary preference of the species, we observed a strong differential rhizopodial activity pattern along the gradient. The highest rhizopodial activity occurred at salinity between 35 and 31 PSU. The species is clearly able to survive long-term exposure to salinities as low as 28, but no rhizopodial activity and signs of cytoplasm degradation were observed in all specimens exposed to 25 PSU. These preliminary observations provide the first direct evidence for the salinity tolerance of N. incompta , indicating a range of salinity that could be plausibly expected to be recorded in the chemistry of fossil shells of the species.